Experiences of and resistance to multiple discrimination in health care settings among transmasculine people of color. - Agénor, Madina.; Geffen, Sophia R.; Zubizarreta, Dougie.; Jones, Raquel.; Giraldo, Shane.; McGuirk, Allison.; Caballero, Mateo.; Gordon, Allegra R. (Tufts University. Tisch Library., 2022)
Keywords: Transgender health, People of color, Health care, Structural barriers, Discrimination, Cissexism, Racism, Weight-based discrimination, Ableism, Resistance.; Springer Open.